Investing in youth vocational training: Professional training programme in the agropastoral and fisheries sectors in Cameroon - Lhoste, Frédéric; Takamgang, Martial Franck (Food and Agricultural Organization of the United Nations, 2021)
Investing in farmers – or agriculture human capital – is crucial to addressing challenges in our agri-food systems. A global study carried out by the FAO Investment Centre and the International Food Research Institute, with support from the CGIAR Research Programme on Policies, Institutions and Markets and the FAO Research and Extension Unit, looks at agriculture human capital investments, from trends to promising initiatives. One of the nine featured case studies is the Support Programme for the Renovation and Development of Professional Training in the Agropastoral and Fisheries Sectors in Cameroon. The programme is part of the training-integration continuum preparing young people for jobs in the agropastoral and fishery sectors and has contributed to strengthening their entrepreneurial and social skills. The success of the model is based on fostering common values centred on the young person’s life project, the involvement of professionals and families in the training, and the building of national expertise in the conception, design, implementation and evaluation of the model. This publication is part of the Country Investment Highlights series under the FAO Investment Centre's Knowledge for Investment (K4I) programme.